(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Аrticle dedicated to the formation and development of the theory «language personality» in language knowledge. language of artistic literature is considered in the context of linguistic-scientific studies. in work the role of language individual in the creation of linguistic worldwide are examined in the case of sokpakbaev’s works. the role of language expressions which format the language character of the writer is based on concrete examples. B.Sokpakbaev is a linguistic person possessing a high art word and played important role in the process of formation of literary Kazakh language. B.Sokpakbaevis an elite person in whom high education, culture, erudition, language competence are inherent. B.Sokpakbaevis a national person, whose diastole shows a national thinking, specificity of the mental world and cultural-historical feature of ethnos